author Jim Pryor Thu, 2 Dec 2010 15:36:53 +0000 (10:36 -0500) committer Jim Pryor Thu, 2 Dec 2010 15:36:53 +0000 (10:36 -0500)
Signed-off-by: Jim Pryor <profjim@jimpryor.net>

index e3ed6f3..1609763 100644 (file)
@@ -314,11 +314,11 @@ Of course, by now you may have realized that we have discovered a new

type 'a tree = Leaf of 'a | Node of ('a tree) * ('a tree);;
-       let tree_unit (a: 'a) = Leaf a;;
+       let tree_unit (a: 'a) : 'a tree = Leaf a;;
let rec tree_bind (u : 'a tree) (f : 'a -> 'b tree) : 'b tree =
match u with
| Leaf a -> f a
-           | Node (l, r) -> Node ((tree_bind l f), (tree_bind r f));;
+           | Node (l, r) -> Node (tree_bind l f, tree_bind r f);;

For once, let's check the Monad laws.  The left identity law is easy:

@@ -393,3 +393,136 @@ called a
that is intended to represent non-deterministic computations as a tree.

+
+What's this have to do with tree\_mondadize?
+--------------------------------------------
+
+So we've defined a Tree monad
+
+       type 'a tree = Leaf of 'a | Node of ('a tree) * ('a tree);;
+       let tree_unit (a: 'a) : 'a tree = Leaf a;;
+       let rec tree_bind (u : 'a tree) (f : 'a -> 'b tree) : 'b tree =
+           match u with
+           | Leaf a -> f a
+           | Node (l, r) -> Node (tree_bind l f, tree_bind r f);;
+
+What's this have to do with the `tree_monadize` functions we defined earlier?
+
+       let rec tree_monadize (f : 'a -> 'b reader) (t : 'a tree) : 'b tree reader =
+           match t with
+           | Leaf a -> reader_bind (f a) (fun b -> reader_unit (Leaf b))
+           | Node (l, r) -> reader_bind (tree_monadize f l) (fun l' ->
+
+... and so on for different monads?
+
+
+
+               env -> 'a;;
+       let unit (a : 'a) : 'a reader =
+               fun e -> a;;
+               fun e -> (fun v -> f v e) (u e);;
+
+We've just beta-expanded the familiar `f (u e) e` into `(fun v -> f v e) (u e)` to factor out the parts where any Reader monad is being supplied as an argument to another function. Then if we want instead to add a Reader layer to some arbitrary other monad M, with its own M.unit and M.bind, here's how we do it:
+
+
+       (* We're not giving valid OCaml code, but rather something
+        * that's conceptually easier to digest.
+        * How you really need to write this in OCaml is more circuitious...
+        * see http://lambda.jimpryor.net/code/tree_monadize.ml for some details. *)
+
+       type ('a, M) readerT =
+               env -> 'a M;;
+       (* this is just an 'a M reader; but that doesn't generalize *)
+
+       let unit (a : 'a) : ('a, M) readerT =
+               fun e -> M.unit a;;
+
+       let bind (u : ('a, M) readerT) (f : 'a -> ('b, M) readerT) : ('b, M) readerT =
+               fun e -> M.bind (u e) (fun v -> f v e);;
+
+Notice the key differences: where before we just returned `a`, now we return `M.unit a`. Where before we just supplied a value `u e` of type `'a reader` as an argument to a function, now we instead `M.bind` the `'a reader` to that function. Notice also the differences in the types.
+
+
+       type 'a identity = 'a;;
+       let unit (a : 'a) : 'a = a;;
+       let bind (u : 'a) (f : 'a -> 'b) : 'b = f u;;
+
+
+The relations between the State monad and the StateT monadic transformer are parallel:
+
+
+       type 'a state =
+               store -> ('a * store);;
+
+       let unit (a : 'a) : 'a state =
+               fun s -> (a, s);;
+
+       let bind (u : 'a state) (f : 'a -> 'b state) : 'b state =
+               fun s -> (fun (a, s') -> f a s') (u s);;
+
+We've used `(fun (a, s') -> f a s') (u s)` instead of the more familiar `let (a, s') = u s in f a s'` in order to factor out the part where a value of type `'a state` is supplied as an argument to a function. Now StateT will be:
+
+
+       type ('a, M) stateT =
+               store -> ('a * store) M;;
+       (* notice this is not an 'a M state *)
+
+       let unit (a : 'a) : ('a, M) stateT =
+               fun s -> M.unit (a, s);;
+
+       let bind (u : ('a, M) stateT) (f : 'a -> ('b, M) stateT) : ('b, M) stateT =
+               fun s -> M.bind (u s) (fun (a, s') -> f a s');;
+
+Do you see the pattern? Where ordinarily we'd return an `'a` value, now we instead return an `'a M` value. Where ordinarily we'd supply a `'a state` value as an argument to a function, now we instead `M.bind` it to that function.
+
+Okay, now let's do the same thing for our Tree monad.
+
+
+       type 'a tree =
+               Leaf of 'a | Node of ('a tree) * ('a tree);;
+
+       let unit (a: 'a) : 'a tree =
+               Leaf a;;
+
+       let rec bind (u : 'a tree) (f : 'a -> 'b tree) : 'b tree =
+           match u with
+           | Leaf a -> f a
+           | Node (l, r) -> (fun l' r' -> Node (l', r')) (bind l f) (bind r f);;
+
+
+       type ('a, M) treeT =
+               'a tree M;;
+
+       let unit (a: 'a) : ('a, M) tree =
+               M.unit (Leaf a);;
+
+       let rec bind (u : ('a, M) tree) (f : 'a -> ('b, M) tree) : ('b, M) tree =
+           match u with
+           | Leaf a -> M.unit (f a)
+           | Node (l, r) -> M.bind (bind l f) (fun l' ->
+                                                       M.bind (bind r f) (fun r' ->
+                                                               M.unit (Node (l', r'));;
+